SEXUALIDADE E DST/AIDS: CONHECIMENTOS E PRÁTICAS DE PROTEÇÃO COM ESCOLARES - Couto, Vânia Aparecida da Silva Figueiredo do (2004)
This work has for general objective to investigate the information regarding sexuality and STD/Aids among students in the city of Rondonópolis (Mato Grosso), observing the behavior of this public for concepts on sexuality and STD, use of condoms and behaviors faced in a virus HIV intense reality. The analysis involves the interpretations, beliefs, images or symbols shared and used for the people in its interaction with sexuality and STD. This manner, the analysis of literature demonstrated that the lack of information on the STD don t usually differs from a situation of salient social differences. The Structuration theory, theoretical framework of the present work, visualizes that the themes like sexuality and the STD s/Aids needs to be part of day-by-day of the young and the adolescents of all the societies, independent of the social or cultural class of the same ones. In this way, it is conceived that school is an important vehicle of information that must be used in all its amplitude, thus assisting in the maintenance of the public health through the prevention of the STD s/Aids. For in such a way, a collection of data was carried to get more details on questions as: Knowledge on sexuality and concept and use of condoms. Among others results founded, it has evidence of the necessity of the school, while privileged space of the information and knowledge, to insert itself in programs that oportunizes the debate and the reflection of the such themes.